Tumour volume as a predictor of postoperative speech impairment in children undergoing resection of posterior fossa tumours: a prospective, multicentre study - Laustsen, Aske Foldbjerg; Avula, Shivaram; Grønbæk, Jonathan; Pizer, Barry; Nyman, Per; Nilsson, Pelle; Frič, Radek; Hjort, Magnus Aasved; Beneš, Vladimír; Hauser, Peter; Pálmafy, Beatrix; Rutkauskiene, Giedre; et al. (Acta neurochirurgica, 2025)
BACKGROUND: Cerebellar Mutism Syndrome (CMS) is a neurological complication of posterior fossa (PF) tumour surgery in children, and postoperative speech impairment (POSI) is the cardinal symptom of CMS. The role of tumour volume on the risk of POSI remains unexplored. This study investigates the association between tumour volume and the risk of POSI. METHODS: We included 360 patients from the European CMS study with available preoperative T1-weighted contrast-enhanced brain MRI. Speech status was assessed within two weeks postoperatively and categorised into three levels: habitual speech, severely reduced speech, and mutism. Tumour volumes were calculated using the BrainLab Elements SmartBrushTM, a semi-automated segmentation tool. We used proportional odds models to estimate the odds ratio (OR) with adjustments for tumour location, pathology, and age. Based on the primary analysis, a risk stratification model for medulloblastoma patients was constructed, and the optimal volume cut-off was determined with Youden's Index. RESULTS: We found no effect of the overall tumour volume on the risk of POSI. This result did not change when adjusted for tumour location, pathology, and age. We found an association between tumour volume of medulloblastoma and the risk of POSI (unadjusted OR of 1.04 per increase in cm3 (95% CI 1.01;1.07, p = 0.01)), which did not change when adjusting for tumour location and age. The risk stratification cut-off for the tumour volume of medulloblastoma was calculated to be 16,5 cm3. Patients with medulloblastoma and preoperative tumour volumes below 16,5 cm3 had an absolute risk of 13% for POSI (low-risk group), whereas patients with preoperative tumour volumes above 16,5 cm3 had an absolute risk of 50% for POSI (high-risk group). CONCLUSION: Our data showed an association between preoperative tumour volume and the risk of POSI in children with medulloblastoma, while no association was found for the volume of other tumour types. We suggest a straightforward cut-off risk model for assessing the risk of POSI in children with medulloblastoma based on preoperative tumour volume. This approach can aid clinicians in informing patients and parents about the complications related to CMS following PF tumour surgery in children. CLINICAL TRIALS: ID NCT02300766 (October 2014).
Keywords: Infratentorial Neoplasms; mužské pohlaví; Male; Cerebellar Neoplasms; Humans; Female; magnetická rezonanční tomografie; pooperační komplikace; lidé; Prospective Studies; Tumor Burden; ženské pohlaví; Postoperative Complications; meduloblastom; mladiství; tumor burden; mutismus; dítě; Child; Adolescent; Magnetic Resonance Imaging; prospektivní studie; infratentoriální nádory; Child, Preschool; Speech Disorders; Mutism; Medulloblastoma; předškolní dítě; nádory mozečku; poruchy řeči